Chemical Composition of Two Endemic Centaurea L. Taxa from Turkey, A Chemotaxonomic Approach - Kilic, Omer; Bagci, Eyup (Taylor & Francis Ltd, 2016)
In this study two endemic Centaurea L. species from Turkey (C. kurdica Reichardt and C. saligna (K.Koch) Wagenitz) which were collected in the similar habitat, have been investigated. The hydro distilled essential oil of aerial parts of C. kurdica and C. saligna were analysed by GC and GC-MS. As a result thirty five and thirty seven components were identified representing 89.0 % and 89.6 % of the oil, respectively. Germacrene D (28.3 %), caryophyllene oxide (10.5 %) and beta-caryophyllene (9.5 %) were detected main compounds of C. kurdica, however caryophyllene oxide (25.2 %), beta-eudesmol (11.5 %) and germacrene D (10.2 %) were detected major constituents of C. saligna. Studied species manufactured many similar constituents in their essential oils that could be verified by the same ecological conditions of their habitat, but also differences were detected that could approve their taxonomic separation. The results have given some clues on the chemotaxonomy of these taxa.
Keywords: Chemotaxonomy; Germacrene D; Centaurea; Essential oil; Caryophyllene oxide